The Stylistic phenomena in Hussein Mardan’s poetry - Sherwan, Ass.Prof PhD Hamed Mardan (Thi Qar Arts Journal, 2023)
Stylistics is one of the subfields of applied linguistics and one of its many branches. It is one of the linguistic phenomena that attempts to explain creativity in the literary text by analyzing its effective linguistic patterns in the text that attempt to move the text from the direct declarative language to the indirect influential creative language. This is only achieved through the effective stylistic arrangements that the creator achieves in the text through deviation and shift from the standard linguistic model. Therefore, the research attempts to investigate the most important stylistic aspects in the poetry of the Iraqi poet Hussein Mardan in order to determine its specificity, uniqueness, and difference from the poets of his generation whom the poet contemporized. Was it able to establish a distinguished poetic creativity that shaped the peculiarity of the poetic experience of the poet Hussein Mardan? Therefore, the research attempts to study the stylistic aspects in Hussein Mardan’s poetry.